PENYULUHAN HIGIENE SANITASI PADA BEBERAPA UPH PERKEBUNAN KOPI DI KABUPATEN NGADA, PROPINSI NUSA TENGGARA TIMUR - G. Ch. Lopulalan, Cynthia (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Hein Namotemo, 2023)
Abstract Increased awareness of cleanliness and higiene in the coffee processing process is the goal of community service projects at three UPH coffee estates in Ngada Regency, NTT Province. Activities at the three coffee UPHs, UPH Papa Taki, UPH Wiu, and UPH Fa Masa, are suggested. FGD activities, counseling, and evaluation are the stages of the activities that are completed. The outcomes of the community service projects demonstrated that the three UPH members were capable of understanding explanations through counseling activities, and the discussion outcomes demonstrated that they would give sanitation higiene factors more attention, particularly those pertaining to the fermentation process and its waste as well as the container and drying process. Some of the challenges that still require joint effort.